Age related grid-wise spatial analysis of choroidal parameters in well characterised healthy population - Meenakshi Kumar; Matt Trinh; Angela Zhang; Xin Wei; Rupesh Agrawal; Lisa Nivison-Smith (Scientific Reports)
Abstract Choroidal vascularity index (CVI) is an image-based metric applied to assess the choroid in disease but poorly explored in natural aging. In this retrospective cohort study, we assessed a single eye of 309 healthy individuals from 20 to 70 + years, and quantified spatial topography of total choroidal area (TCA), luminal area (LA), stromal area (SA) and CVI (LA: TCA) in cluster and standard retinal templates using a semi-automated approach. CVI was found to be greatest in the central vs. periphery (CVIcentral 67.08% [66.85–67.73] vs. CVIperiphery65.68% [65.32–66.01], p < 0.01). In this study, CVI also showed no significant change with age or physiological factors. Area parameters demonstrated greater magnitude in the central versus periphery but with a superior bias: TCAsuperior 0.227mm2 [0.223–0.233] vs. TCAinferior 0.207mm2 [0.201–0.213], p < 0.01.They also showed a linear decline with age (TCA:-0.00112 to -0.00169 mm2/year; LA: -0.00074 to -0.00112 mm2/year; SA: -0.00039 to -0.00056 mm2/year, p < 0.0001), with a higher rate of decline inferiorly (p < 0.001). This study demonstrates that CVI exhibits specific spatial differences across macula, independent of age. It further establishes a comprehensive, normative database of CVI and other choroidal angioarchitecture metrics which is a valuable resource for distinguishing pathological changes from normal age-related variations in future assessments of choroid-involving diseases.